Investigação de poliformismo nos genes das citocinas TNFa, INFg, TGfb, IL-6 e IL-10 em pacientes com febre hemorrágica da dengue - Silva, Francisco Marcio Pereira da (2010)
Currently, Dengue Hemorrhagic Fever - DHF has had a continuous increase in its incidence in general across the country along with the increase of cases has been presenting an alarming fatality rate for DHF. Some conditions have different immune responses in the face of polymorphism in cytokine genes, this study aims to identify genetic factors related to worsening of the disease in patients with DHF. This investigation is the possibility of polymorphisms of cytokines genes: TNF-α -308 G → A, TGF-β codon 10 and codon 25, IL-10 -1082 G → A, -819 C → T, -592 A → C, IL-6-174G → C, and IFN-γ +874 T → A with DHF. The location of cross-sectional study of case-control takes place in Fortaleza, Ceará, Brazil in 2009, with patients who were diagnosed as DHF, laboratory and clinical ways, according to the rules of MS being a total of 48 persons in the DHF group. People who took part in the control group were a total of 85 voluntary blood donors of Hemoce. Samples of material collected, 5mL of blood were used for DNA extraction, using kits PureLink (Invitrogen) and subsequently made the process of typing, which was used Cytgen kits (One-Lambda, Canoga Park, CA, USA ). After the procedures and laboratory tests, it was obtained results as the genotype frequencies of TNF-α, -308 G/G, with predominance in the DHF group (85.4%). In the cytokine IFN-γ +874, the most frequent genotype was T / A in the DHF group (47.9%) in the TGF-β codon 10 and codon 25 genotype was the predominant T/C G/G (41 7%) in group DHF. In IL-6 -174, the most frequent genotype was G/G in the DHF group (58.3%), we note however that despite these frequencies, the cytokines mentioned no association and genotypic nor between allelic polymorphism and worsening of dengue. When analyzing the genotype IL-10 -1082, -819 and -592, we found a predominance of genotype GCC/ACC DHF group (35.5%), and associated with a statistically significant protective factor in the genotype GCC/GCC (21,0%) frequency in the control group. This cytokine showed an association to protect the worsening of the disease. We conclude therefore that the study of polymorphisms of cytokine genes in Dengue Hemorrhagic Fever, showed allelic and genotypic differences in IL-10 as a protective factor.